2012
DOI: 10.1029/2011ja016589
|View full text |Cite
|
Sign up to set email alerts
|

The relation between coronal holes and coronal mass ejections during the rise, maximum, and declining phases of Solar Cycle 23

Abstract: [1] We study the interaction between coronal holes (CHs) and coronal mass ejections (CMEs) using a resultant force exerted by all the coronal holes present on the disk and is defined as the coronal hole influence parameter (CHIP). The CHIP magnitude for each CH depends on the CH area, the distance between the CH centroid and the eruption region, and the average magnetic field within the CH at the photospheric level. The CHIP direction for each CH points from the CH centroid to the eruption region. We focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…The idea is that the flux rope structure is not observed because the CME is deflected away from the Sun-Earth line so that the spacecraft at 1 AU crosses the flank of the corresponding ICME (see Gopalswamy, 2006). We compare the CH influence parameter obtained by Gopalswamy et al (2009) and Mohamed et al (2012) with the flux rope fitting results by Xie, Gopalswamy, and St. Cyr (2013). Xie, Gopalswamy, and St. Cyr (2013) found that on average the MC associated CMEs are deflected towards and the non-MC associated CMEs away from the Sun-Earth line.…”
Section: Introductionmentioning
confidence: 98%
“…The idea is that the flux rope structure is not observed because the CME is deflected away from the Sun-Earth line so that the spacecraft at 1 AU crosses the flank of the corresponding ICME (see Gopalswamy, 2006). We compare the CH influence parameter obtained by Gopalswamy et al (2009) and Mohamed et al (2012) with the flux rope fitting results by Xie, Gopalswamy, and St. Cyr (2013). Xie, Gopalswamy, and St. Cyr (2013) found that on average the MC associated CMEs are deflected towards and the non-MC associated CMEs away from the Sun-Earth line.…”
Section: Introductionmentioning
confidence: 98%
“…CME interactions can also result in CME deflection and merger (Shen et al 2012). In the declining phase, low-latitude coronal holes appear frequently, so CME deflection by such coronal holes becomes important (Gopalswamy et al 2009d;Mohamed et al 2012;Mäkelä et al 2013). The deflections are thought to be caused by the magnetic pressure gradient between the eruption region and the coronal hole (Gopalswamy et al 2010d;Shen et al 2011;Gui et al 2011).…”
Section: Propagation Effects: Deflection Interaction and Rotation Omentioning
confidence: 99%
“…The importance of coronal holes for deflection is featured in many studies (e.g., . Gopalswamy et al (2009a) and Mohamed et al (2012) estimated the magnitude and direction of the resultant magnetic force exerted by all coronal holes present on the solar disk during the time of the CME eruption (defined as the CHIP parameter in Mohamed et al 2012) and compared this with CME trajectories and in situ observations. It was found that CMEs tend to move away from the coronal holes and the CMEs that erupt close to disk center but had large CHIP parameters produced generally complex ICMEs or driverless shocks in the near-Earth solar wind.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%